Ethical considerations for developing pediatric mhealth interventions for teens with socially complex needs. Issue 1 (22nd September 2022) - Bounds, Dawn T.; Stiles‐Shields, Colleen; Schueller, Stephen M.; Odgers, Candice L.; Karnik, Niranjan S.
Abstract: Topic: Mobile Health (mHealth) stands as a potential means to better reach, assess, and intervene with teens with socially complex needs. These youth often face overlapping adversities including medical illness and a history of experiencing adverse childhood experiences (ACEs). Clinicians are faced with navigating ethical decisions when developing mHealth tools for teens who have socially complex needs. Many tools have been developed for adults from the general population. However, despite the development of thousands of mHealth interventions, developers tend to focus on designing for usability, engagement, and efficacy, with less attention on the ethical considerations of making such tools. Purpose: To safely move mHealth interventions from research into clinical practice, ethical standards must be met during the design phase. In this paper we adapt the Four Box Model (i.e., medical indications, preferences of patients, quality of life, and contextual features) to guide mHealth developers through ethical considerations when designing mHealth interventions for teens who present with a medical diagnosis and a history of ACEs. Sources: A review of language, inclusive features, data sharing, and usability is presented using both the Four Box Model and potential scenarios to guide each consideration. Conclusions: To better support designers of mHealth tools we present a framework for evaluating applications to determine overlap with ethical design and are well suited for use in clinical practice with underserved pediatric patients.